Epigenetic Regulation of HIV-1 Sense and Antisense Transcription in Response to Latency-Reversing Agents - Rui Li; Isabella Caico; Ziyan Xu; Mohammad Shameel Iqbal; Fabio Romerio (Non-Coding RNA, 2023)
Nucleosomes positioned on the HIV-1 5′ long terminal repeat (LTR) regulate sense transcription as well as the establishment and maintenance of latency. A negative-sense promoter (NSP) in the 3′ LTR expresses antisense transcripts with coding and non-coding activities. Previous studies identified cis-acting elements that modulate NSP activity. Here, we used the two chronically infected T cell lines, ACH-2 and J1.1, to investigate epigenetic regulation of NSP activity. We found that histones H3 and H4 are present on the 3′ LTR in both cell lines. Following treatment with histone deacetylase inhibitors (HDACi), the levels of H3K27Ac increased and histone occupancy declined. HDACi treatment also led to increased levels of RNA polymerase II (RNPII) at NSP, and antisense transcription was induced with similar kinetics and to a similar extent as 5′ LTR-driven sense transcription. We also detected H3K9me2 and H3K27me3 on NSP, along with the enzymes responsible for these epigenetic marks, namely G9a and EZH2, respectively. Treatment with their respective inhibitors had little or no effect on RNPII occupancy at the two LTRs, but it induced both sense and antisense transcription. Moreover, the increased expression of antisense transcripts in response to treatment with a panel of eleven latency-reversing agents closely paralleled and was often greater than the effect on sense transcripts. Thus, HIV-1 sense and antisense RNA expression are both regulated via acetylation and methylation of lysine 9 and 27 on histone H3. Since HIV-1 antisense transcripts act as non-coding RNAs promoting epigenetic silencing of the 5′ LTR, our results suggest that the limited efficacy of latency-reversing agents in the context of ‘shock and kill’ cure strategies may be due to concurrent induction of antisense transcripts thwarting their effect on sense transcription.